2019
DOI: 10.1093/jnci/djy207
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolic Alterations by HPV Infection: New Dimensions to Head and Neck Cancer Disparity

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer, with high morbidity and mortality. Racial disparity in HNSCC is observed between African Americans (AAs) and whites, effecting both overall and 5-year survival, with worse prognosis for AAs. In addition to socio-economic status and demographic factors, many epidemiological studies have also identified factors including coexisting human papillomavirus (HPV) infection, primary tumor location, and a variety of somatic mutations that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 139 publications
0
52
0
Order By: Relevance
“… 85 In addition to the immunological differences between HPV +ve and HPV −ve tumors, recent studies have shown differential metabolic compartmentalization inside these tumors. 28 While HPV +ve -associated tumors display increased oxidative phosphorylation (OXPHOS) in the tumor core and higher rate of aerobic glycolysis, the inverse is true for HPV −ve tumors. 55 This differential metabolism is associated with increased centrally localized staining of glucose transporter-1 (GLUT1), lactate dehydrogenase-B (LDHB), monocarboxylase transporter 1 (MCT1), and cyclooxygenase 5B (COX5B) in HPV +ve tumors, but more peripheral staining along with the higher concentration of lactic acid in HPV −ve tumors.…”
Section: Tumor Microenvironment Differs In Hpv +Ve mentioning
confidence: 99%
“… 85 In addition to the immunological differences between HPV +ve and HPV −ve tumors, recent studies have shown differential metabolic compartmentalization inside these tumors. 28 While HPV +ve -associated tumors display increased oxidative phosphorylation (OXPHOS) in the tumor core and higher rate of aerobic glycolysis, the inverse is true for HPV −ve tumors. 55 This differential metabolism is associated with increased centrally localized staining of glucose transporter-1 (GLUT1), lactate dehydrogenase-B (LDHB), monocarboxylase transporter 1 (MCT1), and cyclooxygenase 5B (COX5B) in HPV +ve tumors, but more peripheral staining along with the higher concentration of lactic acid in HPV −ve tumors.…”
Section: Tumor Microenvironment Differs In Hpv +Ve mentioning
confidence: 99%
“…The clearest difference is seen in oropharyngeal cancers, in which the human papillomavirus (HPV) has a huge impact on the overall survival of patients. In the oral cavity, the hypopharynx, and the larynx, no impact on the overall survival by HPV has been detected so far [ 30 ]. Moreover, the response towards irradiation is also dependent on the site of origin.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the tumor microenvironment is defined as a very complex ecosystem of cellular and non-cellular components, that are continuously evolving, characterized by unique features, that lead to immunosuppression and diminished anticancer immunity. The cellular components are represented by modified stromal cells (cancer-associated fibroblasts, endothelial cells, adipocytes, neuroendocrine cells, blood cells), and infiltrating immune cells (T cells, B cells, natural killer cells, dendritic cells, macrophages, and myeloid-derived suppressor cells) (25,30,31). The non-cellular components of the tumor microenvironment are proteins of the extracellular matrix (collagen, fibronectin, elastin, laminin, tenascin) that influence proliferation, invasion, metastases, and survival of the cancer cells.…”
Section: Tumor Microenvironment In Head and Neck Cancermentioning
confidence: 99%